Analisis Kesesuaian Penerima dan Penggunaan Dana Bantuan Sosial Pandemi Covid-19 pada Masyarakat Gampong Sapik dan Gampong Air Berudang, Aceh Selatan - Fitria Citra, Suci; Muzalifah, Tari; Ibrahim, Lukman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This research aims to describe the accuracy in the distribution of social assistance during Covid-19 to the people of Gampong Sapik and Air Berudang. It uses a case study with a qualitative approach. Data collection was carried out by observation, interview, and analysis using thematic techniques. The distribution of social assistance has received a positive response from the community because it can help the economy of residents in the midst of the Covid-19 pandemic, even though there are several polemics that have occurred due to incorrect data used and several other obstacles. Based on the Decree of the Minister of Social Affairs of the Republic of Indonesia Number 54 / HUK / 2020 regarding the Implementation of Basic Food Social Assistance and Social Cash Assistance in Handling the Impact of Corona Virus Disease 2019 (Covid-19), the Government realizes social assistance to people affected by Covid-19 which involves the Central Government, regional governments and heads of villages in distributing it to the community.